2002
DOI: 10.1182/blood-2002-03-0990
|View full text |Cite
|
Sign up to set email alerts
|

Favorable prognostic significance of CEBPA mutations in patients with de novo acute myeloid leukemia: a study from the Acute Leukemia French Association (ALFA)

Abstract: The transcription factor C/EBP␣ is crucial for differentiation of mature granulocytes. Recently, different CEBPA gene mutations likely to induce differentiation arrest have been described in nearly 10% of patients with acute myeloid leukemia (AML). In the present study, we retrospectively analyzed the prognostic signifi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
319
7
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 468 publications
(355 citation statements)
references
References 17 publications
20
319
7
7
Order By: Relevance
“…It was significantly lower in CEBPA-mut group than in CEBPA-wt group (means 536.1 and 729.4 respectively, p = 0.039). This result agreed with some previous reports [17,18,20]. However, Frohling et al [21] reported no significant difference in LDH level between both groups.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It was significantly lower in CEBPA-mut group than in CEBPA-wt group (means 536.1 and 729.4 respectively, p = 0.039). This result agreed with some previous reports [17,18,20]. However, Frohling et al [21] reported no significant difference in LDH level between both groups.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly there was non-significant difference in gender distribution between both groups. This finding is in accordance with previous studies [17,18]. Though, Green et al [19] found that younger age was associated with a greater number of mutations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Internal tandem duplications (ITDs) in the FMS-like tyrosine kinase-3 (FLT3) gene,12 partial tandem duplications in the mixed lineage leukemia gene (MLL)34 and enhanced expression of replication factor ectopic virus integration site 15 are all indicators of poor prognosis. In turn, mutation in replication factor CCAAT/enhancer-banding protein α (CEBPA) is associated with good response to therapy 67. With current karyotyping methods, no chromosomal abnormality is found in 40% to 50% of AML patients, and differentiation between different prognostic subtypes in this group of patients by present approaches to molecular genetics seems to be of great importance 489.…”
mentioning
confidence: 99%